Artemisinin-indole and artemisinin-imidazole hybrids: Synthesis, cytotoxic evaluation and reversal effects on multidrug resistance in MCF-7/ADR cells. Issue 9 (1st May 2019) - Hu, Yanping; Li, Na; Zhang, Jiayao; Wang, Ying; Chen, Li; Sun, Jianbo
Graphical abstract: 19 novel artemisinin-indole and artemisinin-imidazole hybrids have been designed and synthesized. The in vitro anti-tumor activity screening results showed that the indole-based hybrids of artemisinin were the effective chemical modification to improve the anticancer activity of artemisinin. The study on cell cycle arrest indicated that compound11c induced MCF-7 cells cycle arrest at G2 phase. The MDR reversal activity in MCF-7/ADR cells indicated that artemisinin-based compounds could reverse multidrug resistance. Highlights: A series of artemisinin derivatives were designed and synthesized. Most of the hybrids showed better anticancer activities than artemisinin. Cell cycle research indicated that11c induced MCF-7 cell cycle arrest at G2 phase. Compound11c showed remarkable MDR reversal activity which reversed adriamycin against MCF-7/ADR cells with IC50 0.76 μM. Abstract: A series of artemisinin derivatives with MDR reversal activity were designed and synthesized. All hybrids were screened to anticancer activities against four human cancer cell lines (A549, MCF-7, HepG-2, MDA-MB-231) and normal human hepatic cell (L02) in vitro . Most of the new compounds showed higher anticancer activities than artemisinin, among which compounds11a and11c displayed superior potency with IC50 6.78 μM and 5.25 μM against MCF-7, respectively. The further research indicated that the most potent11c induced cell cycle arrest at G2 phase in MCF-7. Additionally, compound11c showed remarkable MDR reversal activity which reversed adriamycin against MCF-7/ADR cells with IC50 0.76 μM.